THE INFLUENCE OF EASE, TRUST AND SATISFACTION ON OVO E-WALLET CUSTOMER LOYALTY - Roro Shafira Rizka Amelia; Heriyana; Ikramuddin; Mariyudi (RADJA PUBLIKA, 2024)
Abstract This research aims to see the influence of Convenience, Trust, and the views on OVO E-wallet Customer Loyalty. This research uses primary data obtained by distributing questionnaires to 111 respondents selected using the purposive sampling method. The data analysis method used is using the multiple linear regression method used is using the multiple linear regression method with the help of SPSS. This research shows that convenience has a significant effect on customer loyalty. This identifies that customers who use the OVO E-wallet find it easy because they believe that the OVO E-wallet provides Furthermore, accessing and convenience wherever they are. using Trust has a significant effect on Customer Loyalty, this indicates that customers who use the OVO E-wallet feel confident that the OVO E-wallet can be used by anyone. Furthermore, Satisfcation also has a significant effect on Customer Loyalty, this indicated that customers who use the OVO E-wallet feel satisfied when using it